9514 1404 393
Answer:
6/(2+k)
Explanation:
The change of base formula is ...
![\log_a(b)=(\log(b))/(\log(a))](https://img.qammunity.org/2022/formulas/mathematics/college/98ir5i8ll9izs8b4tscpcni6058ldgpkam.png)
Using this, we can take the logarithm base 2 in the change of base formula for the given expression.
![\log_(20)(64)=(\log_2(64))/(\log_2(20))=(\log_2(2^6))/(\log_2(2^2\cdot5))\\\\=(6)/(\log_2(2^2)+\log_2(5))=\boxed{(6)/(2+k)}](https://img.qammunity.org/2022/formulas/mathematics/college/k1k5atv5k2rg9qijt7faf5kiae7wgdxzv4.png)
__
In addition to the change of base formula, the usual rules of logarithms apply.
![a^b=m\ \longleftrightarrow \ \log_a(m)=b\\\log(ab)=\log(a)+\log(b)](https://img.qammunity.org/2022/formulas/mathematics/college/uyienys7v1sfhet5pm4s4vc9zzr47s6wj3.png)